How you ask is what you get: Willingness-to-pay for a QALY in Germany - Marlis Ahlert; Friedrich Breyer; Lars Schwettmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
We report results of a survey of a representative sample of the German population in which respondents were asked for their willingness-to-pay (WTP) for either an extension of their life or an improvement in their health corresponding to a gain of one quality-adjusted life year (QALY). While one version of the survey exactly copied the questionnaire used in the EuroVaQ project (Pennington et al. 2014), in other versions the wording and the survey technique were modified. The findings show first that Germans have no higher WTP for health gains than other Europeans. Second, the technique of posing the questions plays an important role when respondents are asked to imagine being in hypothetical situations. This clearly refers to the wording of the questions and the survey setting (personal or online interview). But even simple design elements such as offering an explicit option to say No right away greatly affect the answers, as does the position in the questionnaire that a particular question is given. This shows that in any attempts to base health care rationing decisions on the WTP of the population, where the latter is to be elicited using surveys, great care must be taken in designing the questionnaires.
Keywords: I18; 330; willingness to pay; QALY; survey; Germany; EuroVaQ